The role of aerobic capacity and strength levels on wingate performance and lactate concentrations - Al-Nawaiseh, A. M.; Bataineh, M. F.; Kilani, H. A.; Bellar, D. M.; Huffman, O. R.; Judge, L. W. (International Journal of Kinesiology & Sports Science, 2022)
Background: Blood lactate (La-) is commonly assessed in tests of sport performance. Sports that utilize intermittent high intensity effort, monitoring of La- from previous exercise can be useful to document intensity of effort. Objective: The purpose of this study was to investigate the role La- played during successive Wingate (Win) tests and subsequent anaerobic exercise performance. Method: Well-trained, national team athletes from Jordan (n = 31) volunteered to participate. A quasi-experimental design was utilized to test Win performance and La- concentration. All participants engage in two Win tests with one minute rest between sets. La- was collected at four time points (prior to Win test 1, immediately after Win 1, after Win 2 and after a 10 minute recovery period). Results: Findings from a multiple linear regression model (p = 0.032) showed increased levels of La- accumulation as a predictor to higher power and strength (p = 0.046). Conversely, peak aerobic capacity was a predictor for decreasing La- accumulation over time (p = 0.039), which may suggest faster recovery. Conclusion: Anaerobic athletes who participate in short, high intense bouts of exercise may require high intensity training programs to increase aerobic fitness, power output, and optimal performance. Practical applications include optimizing training programs to reflect competition.